2023
DOI: 10.1037/ort0000677
|View full text |Cite
|
Sign up to set email alerts
|

Barriers experienced by emerging adults in discussing their sexuality with parents and health care providers: A mixed-method study.

Abstract: While most parents and health care providers understand the importance of educating young people about their emerging sexuality, many report never discussing sex with the young people in their care. Using data from a survey of 1,193 emerging adults, we applied concept mapping to a corpus of over 2,350 short qualitative responses to two questions: (a) What, if anything, makes it difficult to talk to your parents about sexuality or your sexual health? and (b) What, if anything, makes it difficult to talk to your… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…Constitutional rights do not always equate to women's equality in society, as we have demonstrated (Odera and Mulusa, 2020). Sánchez, Jones, et al (2023) suggested that more state variables are involved in closing this gap; they examine whether state willingness factors that enable systemic discrimination against girls based on their gender or poor state capability and support are to blame for the gender discrepancies in schooling. Findings from a study conducted between 1970 and 2010 in 57 developing nations, including Pakistan, indicate that state willingness-rather than state capacity-is the main cause of gender imbalance in education.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Constitutional rights do not always equate to women's equality in society, as we have demonstrated (Odera and Mulusa, 2020). Sánchez, Jones, et al (2023) suggested that more state variables are involved in closing this gap; they examine whether state willingness factors that enable systemic discrimination against girls based on their gender or poor state capability and support are to blame for the gender discrepancies in schooling. Findings from a study conducted between 1970 and 2010 in 57 developing nations, including Pakistan, indicate that state willingness-rather than state capacity-is the main cause of gender imbalance in education.…”
Section: Literature Reviewmentioning
confidence: 99%